STUDI KOMPARASI METODE FUZZY ARTMAP DAN MULTILAYER PERCEPTRON UNTUK KLASIFIKASI PENGGUNAAN LAHAN MENGGUNAKAN CITRA ALOS AVNIR-2 (Kasus : Sebagian Kabupaten Batang Jawa Tengah) - , FITRA SALEH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Classification methods of digital image, which is currently approachable in integrating the information of land cover and land use, is a classification based on artificial neural network, such as Multilayer Percepton (MLP) and Fuzzy ARTMAP (FAM). These classifications are able to combine spectral and non-spectral data and not require a gaussian training area. The objectives of this study were